A review on prognostics and health management (PHM) methods of lithium-ion batteries. (December 2019) - Meng, Huixing; Li, Yan-Fu
Abstract: Batteries are prevalent energy providers for modern systems. They can also be regarded as storage units for renewable and sustainable energy. Failures of batteries can bring huge losses in terms of personnel, facility, environment, and reputation aspects. Therefore the accurate health estimation and high availability of batteries is urgently required by corresponding users, distributors, and manufactures. Fortunately, prognostics and health management (PHM) technique has been demonstrated the capability of supporting the improvement of the availability and reliability of batteries. In this paper, we gave a review on the state-of-the-art of the PHM study on batteries. We observed the increase of publication related to battery PHM in the past decade (2009–2018), especially in the past five years. Approaches related to battery performance prognostics are categorized into physics-based, data-driven and hybrid classes. Selection of the battery PHM approach requires to take the user requirement, data availability and degradation mechanisms attainability into consideration. Based on the survey, we also proposed research and development perspectives to conduct further studies on the battery PHM, including the approach selection, health management, performance evaluation, uncertainty treatment, application economics, as well as environmental issues. We focused on PHM of lithium-ion batteries, given the fact that several publications discussed other types of batteries (e.g., lead-acid batteries). Highlights: Prognostics methods for lithium-ion batteries are elaborated in three categories. Health management for lithium-ion batteries are discussed. Advantages and drawbacks of PHM methods for lithium-ion batteries are summarized. Future research of PHM methods for lithium-ion batteries has been proposed.